RCD Nuisance Tripping: Whoas Guilty and what Needs to be Done? (Global Journals of Research in Engineering, 2013)
The reasons for nuisance tripping of residual current devices (RCD) are analyzed in the article and the affect of many external factors is discussed. Solutions are described for avoiding faulty tripping of an RCD.
Keywords: residual current device; RCD; nuisance tripping; harmonic; differential current; leakage current